Bach to Brahms : essays on musical design and structure - Beach, David, 1938-; Goldenberg, Yosef, 1967- (Eastman studies in music, 2015)
Bach to Brahms presents current analytic views by established scholars of the traditional tonal repertoire, with essays on works by Bach, Handel, Haydn, Mozart, Beethoven, Schubert, Chopin, and Brahms. The fifteen essays are divided into three groups, two of which focus primarily on the interaction of elements of musical design (formal, metric, and tonal organization) and voice leading at multiple levels of structure. The third group of essays focusses on the 'motive' from different perspectives. The result is a volume of integrated studies on the music of the common-practice period, a body of music that remains at the core of modern concert and classroom repertoire. Contributors: Eytan Agmon, David Beach, Charles Burkhart, L. Poundie Burstein, Yosef Goldenberg, Timothy Jackson, William Kinderman, Joel Lester, Boyd Pomeroy, John Rink, Frank Samarotto, Lauri Suurpää, Naphtali Wagner, Eric Wen, Channan Willner. David Beach is professor emeritus and former dean of the Faculty of Music, University of Toronto. Recent publications include Advanced Schenkerian Analysis, and Analysis of 18th- and 19th-Century Musical Works in the Classical Tradition (co-authored with Ryan McClelland). Yosef Goldenberg teaches at the Hebrew University of Jerusalem and at the Jerusalem Academy of Music and Dance, where he also serves as head librarian. He is the author of Prolongation of Seventh Chords in Tonal Music (Edwin Mellen Press, 2008) and published in leading journals on music theory and on Israeli music.